PENYELESAIAN WANPRESTASI PADA PERJANJIAN KREDIT DENGAN JAMINAN HAK TANGGUNGAN OLEH KOPERASI - Sujana Donandi S (President University, 2016)
In a credit agreement with mortgage in Credit Union (Koperasi SImpan Pinjam/KSP), it is very likely that default happened or the debtor fail to fulfill obligation. The Process of resolving this problem is interesting to be discussed to determine how KSP solves problems of rights and obligations emerging from bad performing loan in which involves morgage. The research is a legal normative-empirical research and the type is descriptive. The result showed that the the resolving of credit with mortgage in KSP could be pursued through the handling procedure, legal effort, and the execution assurance in parate executie or execution without court decisions.